(untitled) (Journal of Nepal Geological Society, 2024)
The geochemical analysis represents a potential approach for understanding sediment provenance, important aspect for source characterisation, weathering pattern and understanding the transport mechanism. This study highlights the significance of major oxides such as CaO, SiO2, Al2O3, Na2O etc. and trace elements such as Al, Fe, Ti, Th etc. as key indicators in providing insights into recent river sediment provenance. These geochemical markers help to unravel sediment source characteristics, weathering, and erosion processes despite the complexities introduced by factors such as grain size sorting, mixing, and hydrodynamic effects. Methods such as the A-CN-K diagram, elemental ratios, and inter-element relationships are particularly powerful for analysing recent sediments, as they help define source geochemistry and recent weathering and erosion patterns. Major oxides and trace element geochemistry are therefore used as a powerful tool for investigating sediment provenance in recent river sediments. This study aims to provide an overview of major and trace element proxies, including the chemical index of weathering and elemental ratios commonly used in provenance evaluation, while assessing their strengths and limitations in determining sediment origin. Their major strength lies in their ability to define source geochemistry and recent weathering and erosion patterns. However, the challenge lies in their inability to distinguish sources with similar lithology. To address this, it is suggested to use the A-CN-K diagram in combination with inter-element ratio relationships for a more comprehensive and accurate analysis.